Bajki i opowiastki na 365 wieczorow - Barth, Doris; Tchorzewska-Kabata, Halina; Brzechwa, Jan, 1898- (Zielona Gora : Elzbieta Jarmolkiewicz, 1995)
A collection of world fairy tales for childlren. Ages 4-10.
Based on the German work: Sandmannlein erzahlt geschichten fur 365 tage. c1978.
Keywords: Fairy tales